Residual stresses VIII : selected, peer reviewed papers from the 8th European Conference on Residual Stresses (ECRS8, 2010), June 26-28, 2010, Riva del Garda, Italy - Scardi, P. (Paolo); Ricardo, Cristy L. Azanza (Materials science forum, 2011)
"The present volume is a collection of the most significant contributions to the 8th European Conference on Residual Stresses (ECRS8), held in Riva del Garda (Trento, Italy) on June 26-28, 2010"--Preface